2021
DOI: 10.4103/ijo.ijo_3533_20
|View full text |Cite
|
Sign up to set email alerts
|

Modified posterior drainage of post-operative suprachoroidal hemorrhage

Abstract: Purpose: To study the anatomical and functional outcomes of trans-conjunctival 23G or 25G cannula-guided modified posterior passive drainage of post-operative suprachoroidal hemorrhage (SCH). Methods: A retrospective study was done on 15 eyes in the last nine years. Vitrectomy with perfluorocarbon liquid injection to push SCH from inside along with 23G or 25G cannula-guided passive drainage of SCH was performed by making multiple sutureless posterior sclerotomies at 10–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Silicone oil provides sufficient filling and plays an anti-inflammatory role, and it could also protect against PVR [ 1 , 2 , 11 ]. Keeping a normal IOP is another function of silicone oil in several studies [ 1 , 2 , 11 , 12 ]. It is reported that persistent hypotony is present in most cases of SCH [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Silicone oil provides sufficient filling and plays an anti-inflammatory role, and it could also protect against PVR [ 1 , 2 , 11 ]. Keeping a normal IOP is another function of silicone oil in several studies [ 1 , 2 , 11 , 12 ]. It is reported that persistent hypotony is present in most cases of SCH [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…(4) Maintain a good working posture. Maintain the most appropriate posture so that the eyes look flat or slightly down at the screen, which relaxes the neck muscles and minimizes the area of the eyeball exposed to the air [12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the current issue of this journal,[ 8 ] the authors have reported perfluorocarbon liquid (PFCL) assisted trans-conjunctival 23-25G cannula-guided drainage of postoperative SCH drainage in 15 eyes. The advantages are sutureless sclerotomies, minimal scarring, and possible placement of multiple cannulas in different quadrants hence more complete drainage.…”
mentioning
confidence: 99%